2016
DOI: 10.1186/s12885-016-2929-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Par3 polarity protein correlates with poor prognosis in ovarian cancer

Abstract: BackgroundPrevious studies have shown that the cell polarity protein partitioning defective 3 (Par3) plays an essential role in the formation of tight junctions and definition of apical-basal polarity. Aberrant function of this protein has been reported to be involved in epithelial–mesenchymal transition (EMT) and cancer invasion. The aim of this study was to examine the functional mechanism of Par3 in ovarian cancer.MethodsFirst, we investigated the association between Par3 expression level and survival of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…In addition, Par3 expression is more significantly upregulated in clinical metastatic PCa samples. Consistently, clinical studies by others in hepatocellular carcinomas [ 9 ], ovarian cancer [ 8 ] as well as clear cell renal cell carcinomas [ 34 ] demonstrated that Par3 acts as a positive regulator and is associated with a poor prognosis. More importantly, the present study showed that Par3 overexpression triggers expression of EMT-related genes such as Zeb1, Snail1, Twist1 and MMP1/9, by inactivation of metastasis-associated Hippo pathway [ 11 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In addition, Par3 expression is more significantly upregulated in clinical metastatic PCa samples. Consistently, clinical studies by others in hepatocellular carcinomas [ 9 ], ovarian cancer [ 8 ] as well as clear cell renal cell carcinomas [ 34 ] demonstrated that Par3 acts as a positive regulator and is associated with a poor prognosis. More importantly, the present study showed that Par3 overexpression triggers expression of EMT-related genes such as Zeb1, Snail1, Twist1 and MMP1/9, by inactivation of metastasis-associated Hippo pathway [ 11 ].…”
Section: Discussionsupporting
confidence: 66%
“…Recent studies by several groups suggest that dislocalization of polarity proteins, Par3 and scribble, for instance, are intricately related to early stages of tumorigenesis via different signal transduction pathways [ 5 7 ]. In addition, it has been revealed that dys-regulation of Par3 is also associated with tumor metastasis and poor prognosis [ 5 , 8 , 9 ]. However, the exact role of Par3 in PCa metastasis is still poorly understood and the underlying molecular mechanisms are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In human cancer, aPKCλ is often overexpressed, whereas for Par3 both increased and decreased expression was observed [ 10 14 ], suggesting that these proteins have opposite actions also in human malignancies. Different mouse tumor models confirmed that aPKCλ serves as a tumor promoter [ 15 ] whereas depending on the tumor settings Par3 indeed can serve both tumor-promoter and suppressor functions [ 4 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] However, in some other tumors, such as liver cancer, ovarian cancer, and renal clear cell carcinoma, PAR3 overexpression supports cancer cell proliferation and is associated with poor cancer prognosis. [8][9][10][11] All these evidences implicated the complex regulatory network of cell polarity and its interaction with oncogenic and tumor suppressor pathways. Recently, PAR3L has been identified as a new member of polarity protein family and exhibits pro-oncogenic activity by maintaining cell stemness and disrupting cell tight junctions.…”
Section: Discussionmentioning
confidence: 99%
“…However, all the growing evidences implicated the oncogenic role of PAR3. Increased PAR3 expression is evident in the metastatic human liver cancer and renal clear cell carcinoma [8][9][10] and correlated with the poor prognosis of ovarian cancer, 11 while knockdown of PAR3 delays the formation of papillomas by decreasing cell proliferation and increasing apoptosis. 12 Previously, a novel homolog of PAR3, PAR3-like protein (PAR3L), has been identified to colocalize with PAR3 at tight junctions.…”
Section: Introductionmentioning
confidence: 99%